(3GdeYGdLGJ GdHbQGWjIs - (3CMeO Hf eMeO CHh GdMSf GdWHQj, fMh (B360 (3g`s ((3ceGd Hf XgjQ GdOjf GHf GMJjGQ GdOjf GdeJWHH s)
(3ChdgG (B:s
(3SGdJfi CSYOc Gddg HWGYJg hhabc deQVGJg hLYdc WGdHkG ddMb hSGdckG efGgLg HQMeJg , Cf CbjO dc TjFG s
(3BNQgG (B:s
(3aCeG CPG cHQ hJQYQY abO JOHjQg ai GdebGdI GdChdi ai GdSjGSI GdNGUI , ajLH Cf jfXQ GdeJYde ajg s
(3GdfSNI HgG MhGTs
(3jJUOQgG agQS JaUjdi dCHhGH GdcJGH GdSJjf hYdjgG ghGeT hebMeGJ dTQM eTcdGJgs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B174 s
Keywords: (3GdWHs